Implementation of Islamic Counseling Spiritual Perspective in Class II-B Corrective Institution Lubuk Pakam North Sumatera - Lubis, Hasan Hamzah; Fakhrurrozi, Fakhrurrozi (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
This study discusses the Implementation of Islamic Counseling Perspective Spirituality in Class IIB Lubuk Pakam Penitentiary. This study uses qualitative research methodology. The results of this study are that the Implementation of Islamic Counseling Perspective Spirituality is 1) making a plan by determining the time, material, and material, and 2) the implementation is by implementing what has been planned, for example with the title